Gallery Walk Strategy in Classroom : Pathway to Improve EFL Students’ Reading Achievement - Agnessia Dwi Elshinta; St. Shabibatul Rohmah (Channing : Journal of English Language Education and Literature, 2017)
This classroom action research was intended to improve the first year students’ reading achievement using gallery walk strategy at SMKN 1 KALIPURO Banyuwangi in the 2016/2017. The subjects of this research were class X NKN 1. This class was determined purposively because most of the students got low score of the reading process and could not achieve the students passing level. The classroom action research consisted of one cycle with four meetings. The data about the students reading achievement were collected through reading exercise, reading test and observation. Based on the observation in the first meetings, there were 60% or 19 out of 32 students who showed a positive attitude in teaching learning process through gallery walk strategy. Then, it increases to 87% or 28 students who showed a positive attitude in teaching learning process using gallery walk strategy in the last meeting. The result of reading exercise from first meeting until the last meeting also increase, from 50% or 16 students in the first meeting to 75% or 24 students in the last meeting. The result of reading test in cycle one showed that there were 26 students or 81% of the students achieved the target. To sum up, the use of gallery walk strategy is effective to improve students’ reading achievement and students’ participation in teaching and learning process